Interaksi Subak Jatiluwih dengan Pariwisata - NI LUH PUTU DIAH AYU HARTARI PUTRI; WAYAN SUDARTA; I GUSTI AYU OKA SURYAWARDANI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2017)
Subak of Jatiluwih Interaction with Tourism Jatiluwih is well known as a world-recognized agricultural and tourism area. Thiscondition reflects a good interaction between agriculture which in this case isrepresented by subak/organization of irrigation with tourism i.e. is represented bytourism actors. Data collection in the field shows different conditions, namely thefinding of land conversion and job transformation from subak members. Both ofthese conditions indicate an interaction between subak and tourism actors. Thepurpose of the study discusses the form of interaction between subak with tourism inJatiluwih, and the impact of interaction on the existence of subak. The analyticalmethod used to discuss the research problem is descriptive qualitative analysis.Qualitative descriptions are applied to information provided by the subak membersand tourism stakeholders. The findings showed that associative interaction was moreprominent than the dissociative interaction. Cooperation of Subak Jatiluwih withtourism in the permission of utilizing the subak area for the agency management ofJatiluwih Tourism Destination Area is meant to be the generator income because ofits natural beauty. In contrast, Subak Jatiluwih needs for compensation for anydamages to rice field and fund for religious ceremony of subak, namely theceremony of Ngusaba Ayu and fund for cleaning the subak irrigation channel. Thedissociative interaction can still be declared low because it can still be wellanticipated. Suggestions that can be given that the contribution to the subak need tobe considered for the subak given a more feasible contribution because it isconsidered so far not meet the feasible criteria.